Фрагмент пізньосередньовічної надмогильної плити з Королівського замку Нялаб: зброєзнавчий аналіз - Калініченко, Віталій; Прохненко, Ігор (Київ, Інститут історії України НАН України, 2020)
A fragment of a knight’s tombstone, a massive piece of marbled limestone bas-relief, has been discovered at the floor level under the walls’ debris during a study of the room 3 of the castle of Nyaláb in Korolevo. Similar monuments appeared in Europe on the edge of 13-14th centuries, while for Carpathian region they were known since the last third of 15th century. The tombstones, depicting a knight at his full height on his deathbed, were wide-spread in Hungarian Kingdom during the last years of the king Corvin Mátyás reign and were connected to the workshop of the king’s court sculptor from Italy Giovanni Dalmata. Important in this aspect is the weapons analysis of the above image. On the head of the deceased – a helmet like a salad. Despite the damage to the bas-relief, the rivets with which the visor was attached to the helmet are clearly visible in the area of the temples. The helmet also stands out well in the image. Only on the basis of the characteristic features of the helmet, the tombstone can be dated to the middle of the 15-20s of the 16th century.
A Fragment of a Medieval Tombstone from the castle of Nyaláb
Keywords: археологічні дослідження; Закарпатська область; Королівський замок Нялаб; надмогильна плита; зброєзнавство; пізнє середньовіччя